(untitled) (CIPEEX, 2025)
The technical and scientific professional development in the practice of body anamnesis is essential for the quality and precision of care in various areas of health. Body history involves the detailed collection of information about the patient’s physical state, allowing for a thorough assessment that is crucial for the diagnosis, prevention, and treatment of various conditions. In recent years, the growth of interest in this area has motivated the publication of new studies and guidelines aimed at improving the skills of professionals. This narrative review aims to explore the technical and scientific development of health professionals in the practice of body anamnesis, based on scientific articles published in the last five years. The objective is to identify the main trends, challenges, and advances that have impacted this practice. For the construction of this review, searches were performed in databases such as PubMed, Scielo, and Google Scholar. The terms used included "body anamnesis," "professional development," "technical skills," and "continuing education." Articles published between 2018 and 2023 that address the technical and scientific development in the practice of body anamnesis were selected. The reviewed articles indicate that technical and scientific development in body anamnesis is an area in constant evolution, with increasing emphasis on continuing education and specific training for the practice. Studies highlight the importance of continuous training of health professionals to ensure an accurate and comprehensive anamnesis. In addition, new technologies and methods of body assessment have been incorporated, promoting significant advances in clinical practice. The literature also points to challenges such as the lack of standardization in anamnesis techniques and the need for greater integration between scientific and practical areas. The technical and scientific professional development in body anamnesis is essential to improve the quality of health care. The review of the last five years shows that, although there have been significant advances, there are still challenges to be overcome, such as the standardization of techniques and the need for continuing education. Investments in training and the integration of new technologies are crucial for improving this practice, benefiting both professionals and patients.